Exchange in the Absence of Legal Enforcement: Reputation and Multilateral Punishment under Uncertainty. (9th January 2019) - Hajikhameneh, Aidin; Rubin, Jared
Abstract: Principal–agent problems can reduce gains from exchange available in long distance trade. One solution historically used to mitigate such problems is multilateral punishment, whereby groups of principals jointly punish cheating agents by giving them bad reputations. But how does such punishment work when there is uncertainty regarding whether an agent actually cheated or was just the victim of bad luck? And how might such uncertainty be mitigated—or exacerbated—by non-observable, pro-social behavioral characteristics? We address these questions by designing a simple modified trust game with uncertainty and the capacity for principals to employ multilateral punishment. Our experimental results indicate that a modest amount of uncertainty has little effect on overall welfare: while part of the surplus is destroyed by uncertainty, principals are also more willing to trust agents with bad reputations, thereby increasing the frequency of welfare-enhancing exchange. ( JEL C91, C92, D02, D83, F10, N70)